RUANG KERJA BERSAMA PADA ERA NEW NORMAL - Medina, Ninda; Aufa, Naimatul; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Currently the world including Indonesia has entered the era of the Industrial Revolution 4.0 which forms a new order where humans and technology coexist and always collaborate. In addition, Indonesia is experiencing an increase in demographics, especially in the productive age group such as the millennial generation and generation Z. In line with the development of the Industrial Revolution 4.0 and the increase in the population of the millennial generation, the world is faced with the Covid-19 pandemic situation which is increasingly accelerating the development of the Industrial Revolution 4.0. On the other hand, the Covid 19 pandemic has also adversely affected the productivity of workers due to the Lockdown and Work From Home policies. For that, we need a place that is able to support the work style of millennials, namely Coworking Space. The Healthy Architecture concept with the Adaptive Architecture method applied to this design aims to create a healthy and safe work environment through its architectural design in order to avoid the spread of Covid-19. The application of this concept is expected to be able to help the community to be better prepared to face other health challenges in the future through healthy habits created through its architectural design.